(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
substantiation of the possibility of application and development of a method of photodynamic therapy using methylene blue for intraoperative sanitation of the abdominal cavity in generalized peritonitis.